2009
DOI: 10.1016/j.mambio.2009.05.010
|View full text |Cite
|
Sign up to set email alerts
|

A long term study of small mammal populations in a Brazilian agricultural landscape

Abstract: Long-term monitoring of small mammal populations is very important to understand the variations in temporal abundance on a large time scale, which are related to ecological, economic and epidemiological phenomena. The aim of this study is to monitor the populations of the marsupials Didelphis aurita and Philander frenatus and the rodents Nectomys squamipes, Akodon cursor and Oligorysomys nigripes in a locality of typical Brazilian rural landscape, Sumidouro Municipality, Rio de Janeiro State, Brazil. A mark-re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
12
0
5

Year Published

2012
2012
2023
2023

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 30 publications
(19 citation statements)
references
References 52 publications
2
12
0
5
Order By: Relevance
“…These population dynamics patterns agree with other studies on Sigmodontinae ecology in both Atlantic Forest landscape types, Mixed Ombrophilous Forest, 45,48,49 and Dense Ombrophilous Forest. 44,47,74,75 Hantavirus exhibited a seasonal pattern with higher prevalence in spring/summer, when population sizes were lower and both reproductive activity and numbers of adults were higher. This pattern was also witnessed for other hantavirus genotypes in North 52,56 and South America.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…These population dynamics patterns agree with other studies on Sigmodontinae ecology in both Atlantic Forest landscape types, Mixed Ombrophilous Forest, 45,48,49 and Dense Ombrophilous Forest. 44,47,74,75 Hantavirus exhibited a seasonal pattern with higher prevalence in spring/summer, when population sizes were lower and both reproductive activity and numbers of adults were higher. This pattern was also witnessed for other hantavirus genotypes in North 52,56 and South America.…”
Section: Discussionmentioning
confidence: 99%
“…47,75 This low abundance and instability on O. nigripes populations may be playing an important role to keep JUQV-like at low frequency.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Human populations were also diagnosed and treated. With this design, we obtained results that have enabled us to raise the small mammal fauna of the area (D'Andrea et al, 1999), understand the pattern of population dynamics of the water-rat (Bonecker et al, 2009;D'Andrea et al 2007;Gentile et al 2000) and its habitat use (Gentile & Fernandez 1999), understand aspects of the relationship between S. mansoni and N. squamipes Gentile et al, 2006), and adapt procedures and techniques to local particularities. In Pamparrão, which is a low endemicity area, the population dynamic study of the waterrat showed that it reproduced throughout the year, predominantly during the rainy periods.…”
Section: Eco-epidemiologic Monitoring -The Rodent As a Focus Transmismentioning
confidence: 99%
“…In the Encanto locality, where schistosomiasis present at a medium endemicity, another phase of the study was conducted over four years to evaluate the effects of chemotherapy treatment in the infected human population on the rate of rodent infection and to compare diagnostic methods. During this phase, we also studied the population dynamics of the rodent N. squamipes, the infection rate of schistosomiasis on the water-rat populations and its change over time, and different methods for S. mansoni diagnosis (Bonecker et al, 2009;Gentile et al, 2006). The population dynamics of N. squamipes were in accordance with other studies and with the Pamparrão study, where the reproduction of the animals occurred throughout the year but primarily during rainy periods, a trend that is related to the close association of this rodent to resources found in water (Ernest & Mares, 1986;Gentile et al, 2000).…”
Section: Eco-epidemiologic Monitoring -The Rodent As a Focus Transmismentioning
confidence: 99%